2020
DOI: 10.1186/s12883-020-01662-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum α-synuclein and IL-1β are increased and correlated with measures of disease severity in children with epilepsy: potential prognostic biomarkers?

Abstract: Background: The search for noninvasive biomarkers of neuroinflammation and neurodegeneration has focused on various neurological disorders, including epilepsy. We sought to determine whether α-synuclein and cytokines are correlated with the degree of neuroinflammation and/or neurodegeneration in children with epilepsy and with acquired demyelinating disorders of the central nervous system (CNS), as a prototype of autoimmune neuroinflammatory disorders. Methods: We analyzed serum and exosome levels of α-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
3
24
1
3
Order By: Relevance
“…Pediatric epilepsy is another persistent brain disorder that exhibits behavioral and cognitive challenges, including intellectual dysfunctions, behavioral problems, and attention deficits [25,59]. In a clinical study of children with epilepsy, upregulated expression of serum α-synuclein was observed, with a positive correlation to the measures of disease severity, suggesting that it may present a plausible prognostic biomarker of the neurodegenerative process [25]. In addition, serum α-synuclein levels were positively correlated to exosome α-synuclein levels, the presumptive fraction of the cerebrospinal fluid (CSF).…”
Section: Alpha-synuclein-mediated Neurodegeneration: Implication In Epileptogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric epilepsy is another persistent brain disorder that exhibits behavioral and cognitive challenges, including intellectual dysfunctions, behavioral problems, and attention deficits [25,59]. In a clinical study of children with epilepsy, upregulated expression of serum α-synuclein was observed, with a positive correlation to the measures of disease severity, suggesting that it may present a plausible prognostic biomarker of the neurodegenerative process [25]. In addition, serum α-synuclein levels were positively correlated to exosome α-synuclein levels, the presumptive fraction of the cerebrospinal fluid (CSF).…”
Section: Alpha-synuclein-mediated Neurodegeneration: Implication In Epileptogenesismentioning
confidence: 99%
“…In addition, serum α-synuclein levels were positively correlated to exosome α-synuclein levels, the presumptive fraction of the cerebrospinal fluid (CSF). Interestingly, in children with epilepsy, there was a significant correlation of exosomal α-synuclein with serum interleukin (IL)-6 levels, reflecting that exosomal α-synuclein may contribute to the neurotoxic cycle of neuroinflammation in epilepsy patients [25] based on its ability to directly activate the astrocytic production of IL-6 [60].…”
Section: Alpha-synuclein-mediated Neurodegeneration: Implication In Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…31 In the clinical aspect, Shi et al indicated that IL-1β levels in cerebrospinal fluid were higher in the epileptic pediatric population than in the controls; 39 Vezzani et al demonstrated that secretion and release of IL-1β was remarkedly upregulated in cerebrospinal fluid and serum of epilepsy patients after tonic-clonic seizures; 40 Ichiyama et al showed that IL-1β levels were remarkedly increased in cerebrospinal fluid of patients with febrile seizures; 41 Uludag et al showed that serum IL-1β levels were significantly elevated in patients with temporal lobe epilepsy or extra-temporal lobe epilepsy, and there is no statistical difference in the degree of elevation of IL-1β between these two groups; 42 Zhang et al found that upregulated expression of IL-1β was independently associated with increased risk of seizure recurrence after the first epileptic seizure in ischemic stroke patients, and moreover the predictive value of IL-1β expression levels for seizure recurrence was high; 18 Choi et al found that serum IL-1β levels were significantly associated with disease severity in children with epilepsy, suggesting the potential of IL-1β as a prognostic biomarker for childhood epilepsy. 43 In this study, the serum IL-1β level was an independent risk factor for PSE in ischemic stroke patients (OR: 1.457, 95% CI: 1.215-1.894) and had a medium predictive value for PSE (AUC: 0.811). The SeLECT score is a new practical prognostic tool to predict the risk of PSE, integrating five items: early seizures, severity of stroke, cortical involvement, territory of middle cerebral artery involvement and large-artery atherosclerotic aetiology.…”
Section: Discussionmentioning
confidence: 55%
“…Correlation analysis showed that serum levels of IL-1 β were significantly associated with disease severity in children with epilepsy. This set of evidence highlights that serum IL-1 β may represent a biomarker for epilepsy as an ongoing neuroinflammation [ 21 ]. An observational study [ 22 ] reported that IL-6 levels in both serum and CSF were elevated in refractory status epilepticus and acute seizures.…”
Section: Blood Biomarkersmentioning
confidence: 99%